Mulheres em situação de violência na favela de Paraisópolis: possibilidades de luta e resistência - Silva, Eliana Pereira (2014)
The object of this study is the analysis and the apprehension of violence as one of the expressions of this social issue and its interrelationship with the categories Class and Gender and Race, by means of the delimitation of the universe of the daily lives of a number of women who live in the Paraisópolis community (a neighborhood in São Paulo city), their perception and experience, as well as the ways they forge their strategies of survival and possibilities of resistance, their conditions, and precise determinations of social reality. The aim of this research is to understand the perception of these women regarding their experiences with violence, the violence specifically towards them, and the meaning attributed to their experiences, and the ways in which they organize themselves, resist (or not) to the various forms of violence. We start from the conception of violence as a category which is saturated by determinations and contradictions, which can be apprehended only by means of the analysis of their specific conditions. From this perspective, we opted for conducting a qualitative research, specifically in the construction of oral narratives of the women who live in the Paraisópolis community, along with a group interview with leaders of the Association of Women in the region. The conduction of the research included a description and an analysis of the territory of Paraisópolis and its characteristics in relation to violence, and how the various kinds of violence affect directly the daily lives of the women. By means of interviews and the construction of the oral narratives, we approached the voice and the perception of the subjects, the way they elaborate their own experience and their possibilities of resistance in their daily lives. These are women who, despite all the difficulties, build, from their daily life, strategies of survival, resistance, and ways of life. They subvert their daily life and recognize themselves as subjects, by means of inclusion in collective actions and activities, solidarity networks and in the construction of several survival strategies